Differential Susceptibility to Particulate Matter-Induced Cardiac Remodeling and Senescence: A Comparative Study in Young and Aged Mice - Dunia Waked; Gabriel Henrique Rodella Guedes; Raissa Macedo; Paulo Hilário Nascimento Saldiva; Mariana Matera Veras; Ana Paula Cremasco Takano (Atmosphere)
Background: Epidemiological and toxicological studies have shown that inhalation of particulate matter (PM), a major component of air pollution, is associated with the development of cardiovascular diseases (CVDs). Cellular senescence and other aging mechanisms are also key factors in the development and progression of CVD. This study aims to investigate age-related susceptibility to cardiac remodeling and senescence due to PM exposure. Methods: Young and old male C57BL/6 mice were exposed to filtered or polluted air for six months using an ambient particle concentrator. Cardiac hypertrophy, fibrosis, and markers of cellular senescence (p53, p21, p-H2AX, and lipofuscin) in the myocardium were evaluated in the experimental groups. Results: PM exposure induces signs of cardiac remodeling, including cardiomyocyte enlargement and increased fibrosis, in young mice, along with elevated p53 expression. However, no significant alterations in cardiac structure or senescence markers were observed between aged mice exposed or not to PM. Conclusions: Our study indicates that younger individuals may be more vulnerable to the cardiovascular effects of chronic PM than older individuals exposed later. Further studies are needed to explore detailed mechanisms of this age-dependent response.